Pengaruh Model Pembelajaran Team Games Tournament Terhadap Hasil Belajar Siswa Kelas V Pada Subtema 1 Peristiwa Kebangsaan Masa Penjajahan Di SD Negeri 091273 Karang Bangun - Nurhayati Pakpahan; Rio Parsaoran Napitupulu; ⁠Muktar B. Panjaitan (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study to determine the effect of Team games tournament model on student learning outcomes in subtheme 1 Class V SD Negeri 091273 Karang bangun. This study is a pre-experimental study using one group pretest-posttest design, the sample of this study was 25 people. Data collection technique is a test. By doing the pretest got an average result of 65.92, then given treatment after treatment using the Team games tournament model so that it gets a posttest with an average value of 91.76. With the value obtained, the value of the postest has a higher average than the pretest. After doing the post test, the researchers conducted an n-gain Test got an n-gain score of 0.7660 categorized as high and the hypothesis test got a value of 27,562. T test results obtained by thitung = 27,562 with a significance level of 0,000. since the significant probability is much smaller than 0.05 i.e. 0.000 and thitung = 27,562 > ttable = 1,711 then HO is rejected and Ha is accepted. This shows that there is an influence of the Team games tournament learning model on the learning outcomes of Class V students on the theme 7 events in life and subtheme 1 national events of the colonial period on learning 1 and 2 in Class V at SD Negeri 091273 Karang bangun academic year 2023/2024.